MASYARAKAT EKONOMI ASEAN (MEA) 2015 DAN TANTANGAN NEGARA KESEJAHTERAAN - Fathoni Fathoni (UNIB Press, 2015)
ABSTRACT Indonesia is a sovereign state. The word here is not only sovereign denotatively meaning that the state government does not have power under the jurisdiction of another country. State government meant for the welfare of the people. When it is associated with free competition among countries, it can be more about the role of the state in protecting its citizens in order to avoid what is, according to Hobbes as